Relevansi Kontemporer Qs. Al-Masad : Analisis Karakter Abu Lahab dan Ummu Jamil Prespektif Tafsir Al-Azhar - Nofa Nur Rahmah Susilawati; Ismail Ismail (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study aims to re-examine Surah Al-Masad through the lens of Buya Hamka's Tafsir Al-Azhar, with the objective of moving beyond a textual reading to uncover its historical context and contemporary relevance. Employing a qualitative library research method, this study adopts a thematic (maudhu'i) interpretation approach. The analysis is conducted systematically through textual, historical, and contextual stages, as well as interdisciplinary approaches from social sciences, politics, and media studies, framed within an integral theology-ethics perspective. The results demonstrate that Surah Al-Masad transcends a mere historical narrative; it presents Abu Lahab as an eternal archetype of the systemic collapse that results from hostility towards the truth. Hamka's interpretation successfully bridges the textual meaning with social reality, revealing the surah's significant contemporary relevance when examined through an interdisciplinary lens. The novelty of this research lies in its integrative analysis that synthesizes theological, ethical, and sociological dimensions within Hamka's framework. The findings imply that policymakers and community leaders can derive strategic insights for constructing resilient da'wah narratives and ethical frameworks to counter modern opposition effectively.